International society of sports nutrition position stand: ketogenic diets - Alex Leaf; Jeffrey A. Rothschild; Tim M. Sharpe; Stacy T. Sims; Chad J. Macias; Geoff G. Futch; Michael D. Roberts; Jeffrey R. Stout; Michael J. Ormsbee; Alan A. Aragon; Bill I. Campbell; Shawn M. Arent; et al. (Journal of the International Society of Sports Nutrition)
Position statement The International Society of Sports Nutrition (ISSN) provides an objective and critical review of the use of a ketogenic diet in healthy exercising adults, with a focus on exercise performance and body composition. However, this review does not address the use of exogenous ketone supplements. The following points summarize the position of the ISSN:1. A ketogenic diet induces a state of nutritional ketosis, which is generally defined as serum ketone levels above 0.5 mM. While many factors can impact what amount of daily carbohydrate intake will result in these levels, a broad guideline is a daily dietary carbohydrate intake of less than 50 grams per day.2. Nutritional ketosis achieved through carbohydrate restriction and a high dietary fat intake is not intrinsically harmful and should not be confused with ketoacidosis, a life-threatening condition most commonly seen in clinical populations and metabolic dysregulation.3. A ketogenic diet has largely neutral or detrimental effects on athletic performance compared to a diet higher in carbohydrates and lower in fat, despite achieving significantly elevated levels of fat oxidation during exercise (~1.5 g/min).4. The endurance effects of a ketogenic diet may be influenced by both training status and duration of the dietary intervention, but further research is necessary to elucidate these possibilities. All studies involving elite athletes showed a performance decrement from a ketogenic diet, all lasting six weeks or less. Of the two studies lasting more than six weeks, only one reported a statistically significant benefit of a ketogenic diet.5. A ketogenic diet tends to have similar effects on maximal strength or strength gains from a resistance training program compared to a diet higher in carbohydrates. However, a minority of studies show superior effects of non-ketogenic comparators.6. When compared to a diet higher in carbohydrates and lower in fat, a ketogenic diet may cause greater losses in body weight, fat mass, and fat-free mass, but may also heighten losses of lean tissue. However, this is likely due to differences in calorie and protein intake, as well as shifts in fluid balance.7. There is insufficient evidence to determine if a ketogenic diet affects males and females differently. However, there is a strong mechanistic basis for sex differences to exist in response to a ketogenic diet.